2020
DOI: 10.21203/rs.2.23146/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

circRNA-UBAP2 promotes the proliferation and inhibits apoptosis of ovarian cancer though miR-382-5p/PRPF8 axis

Abstract: Objective: circular RNAs (circRNAs) have been reported to be essential regulators of multiple malignant cancers. However, the functions of circRNAs in ovarian cancer need to be further explored. The aim of our study is to explore the role of circRNA-UBAP2 in ovarian cancer and its mechanism. Results: circRNA-UBAP2 was upregulated in ovarian cancer tissues and cell lines. Knockdown of circRNA-UBAP2 inhibited cell proliferation and promoted cell apoptosis, but circRNA-UBAP2 overexpressed got opposite results. In… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Overexpression of miR-144 has a reverse effect on Circ-UBAP2 tumorigenesis [56]. Another study conducted on circ-UBAP2 showed that cell proliferation increases upon overexpression of circ-UBAP2 and cell apoptosis decreases via the miR-382-5p/PRPF8 pathway [57]. Deng et al found that ESRP1 overexpression is regulated by circ-0005585 via sponging of miR-15a, miR-15b, miR-16, miR-23a and miR-23b, which inhibited cancer cell migration and metastasis through alternative splicing of two cytoskeleton-associated proteins: EPB41L5 and Rac1 [58].…”
Section: Circrnas and Their Roles In Oc Pathogenesismentioning
confidence: 99%
“…Overexpression of miR-144 has a reverse effect on Circ-UBAP2 tumorigenesis [56]. Another study conducted on circ-UBAP2 showed that cell proliferation increases upon overexpression of circ-UBAP2 and cell apoptosis decreases via the miR-382-5p/PRPF8 pathway [57]. Deng et al found that ESRP1 overexpression is regulated by circ-0005585 via sponging of miR-15a, miR-15b, miR-16, miR-23a and miR-23b, which inhibited cancer cell migration and metastasis through alternative splicing of two cytoskeleton-associated proteins: EPB41L5 and Rac1 [58].…”
Section: Circrnas and Their Roles In Oc Pathogenesismentioning
confidence: 99%
“…The expression of these molecules was associated with atherosclerotic vascular disease risk [ 49 ]. Importantly, numerous circRNAs were found to be overexpressed in the serum of OC patients, whereas others, such as circ_0051240, circ-HIPK3 (homeodomain interacting protein kinase 3), and circRNA-UBAP2 (ubiquitin associated protein 2), were implicated in the control of OC cells malignant behavior [ 50 , 51 ]. CircRNAs are more stable in cells than their linear counterparts due to their covalent closed-loop structure.…”
Section: Lncrna Genes and Their Expression Patternsmentioning
confidence: 99%
“…Due to the lack of 3' poly (A) tail and 5' end cap, circRNAs are resistance to RNase R and are highly stable in vivo compared with linear RNA transcript [7]. Many studies have reported that circRNAs can serve as molecular sponge of microRNAs (miRNAs) to modulate gene expressions in the progression of cancers [8][9][10][11][12]. For example, circ-WHSC1 promotes the development of endometrial cancer by targeting miR-646 and up-regulating the expression of NPM1 [10].…”
Section: Introductionmentioning
confidence: 99%